Financial planning: Theory and practice - Sahu, Anandi P.; Mittra, Sid; Rai, Shailendra kumar (New Delhi Atlantic publishers & distributor (p) Ltd., 2024)
An all-encompassing companion to understanding the nuances of the financial planning process. This comprehensive text is the outcome of decades of teaching and practical experience of the authors in the field of financial planning. It is the first Indian adaptation of Practising Financial Planning for Professionals (now in its 11th edition in the United States), which is already a classic textbook.